Estimasi Model Parametrik Komponen Feedback, Feedforward, dan Nois pada Sistem Lup Tertutup dengan Teknik Extended Least Square - Harijono A. Tjokronegoro (Institute for Research and Community Services (LPPM) ITB, 2003)
In this paper is considered a direct estimation technique of model parameters of components (subsystems) of a feedback system using an extended least squares algorithm. There are three components of system may be estimated, feedback, feedforward, and noise. It has been assumed that the system considered was linear and time invariant. A common estimation technique for closed loop system is indirect, and under assumption that only one component will be estimated while the other components in the closed loop are known. The analysis shows that the proposed technique is unnbias. In the proposed structure, one of the components in the closed loop system maybe unstable, as long as the closed loop system is stable.